Swisscontact uses the Women’s Empowerment in Agriculture Index to develop and implement gender and social inclusion strategies in agricultural value chains in southern Honduras - CGIAR Research Program on Policies, Institutions, and Markets (2021)
In the Gulf of Fonseca, Honduras, the NGO Swisscontact applied the Women's Empowerment in Agriculture Index (WEAI), Women’s Empowerment in Livestock Index (WELI) and WEAI for Market Inclusion (pro-WEAI+MI) to identify and implement actions to improve women's levels of empowerment in the production and processing links of three value chains of significant importance for the economic and social development of the region and country: cashew, dairy and fruits. These actions are included in strategies published and disseminated in 2021.